Liquid chromatography-tandem mass spectrometry methods for quantification of total and free antibiotic concentrations in serum and exudate from patients with post-sternotomy deep sternal wound infection receiving negative pressure wound therapy - Brozmanová, Hana; Šištík, Pavel; Ďuricová, Jana; Kacířová, Ivana; Kaňková, Klára; Kolek, Martin (Clinica chimica acta; international journal of clinical chemistry, 2024)
BACKGROUND: Systemically administered antibiotics are thought to penetrate the wounds more effectively during negative pressure wound therapy (NPWT).To test this hypothesis total and free antibiotic concentrations were quantified in serum and wound exudate. METHODS: UHPLC-MS/MS methods were developed and validated for the determination of ceftazidime, cefepime, cefotaxime, cefuroxime, cefazolin, meropenem, oxacillin, piperacillin with tazobactam, clindamycin, ciprofloxacin, sulfamethoxazole/trimethoprim (cotrimoxazole), gentamicin, vancomycin, and linezolid. The unbound antibiotic fraction was obtained by ultrafiltration using a Millipore Microcon-30kda Centrifugal Filter Unit. Analysis was performed on a 1.7-µm Acquity UPLC BEH C18 2.1 × 100-mm column with a gradient elution. RESULTS: The validation was performed for serum, exudates and free fractions. For all matrices, requirements were met regarding linearity, precision, accuracy, limit of quantitation, and matrix effect. The coefficient of variation was in the range of 1.2-13.6%.and the recovery 87.6-115.6%, respectively. Among the 29 applications of antibiotics thus far, including vancomycin, clindamycin, ciprofloxacin, oxacillin, cefepime, cefotaxime, cotrimoxazole, and gentamicin, total and free antibiotic concentrations in serum and exudate were correlated. CONCLUSION: This method can accurately quantify the total and free concentrations of 16 antibiotics. Comparison of concentration ratios between serum and exudates allows for monitoring individual antibiotics' penetration capacity in patients receiving NPWT.
Keywords: Trimethoprim, Sulfamethoxazole Drug Combination; Sternotomy; Chromatography, Liquid; kombinace léků trimethoprim a sulfamethoxazol; cefotaxim; Exudate; Method validation; Gentamicins; vysokoúčinná kapalinová chromatografie; sternotomie; tandemová hmotnostní spektrometrie; antibakteriální látky; Wound Infection; infekce v ráně; ciprofloxacin; Clindamycin; gentamiciny; Vancomycin; chromatografie kapalinová; Chromatography, High Pressure Liquid; exsudáty a transsudáty; Ciprofloxacin; lidé; Anti-Bacterial Agents; klindamycin; Humans; Cefotaxime; Total and free antibiotic concentration; Exudates and Transudates; Negative pressure wound therapy; Serum; cefepim; Cefepime; Negative-Pressure Wound Therapy; Cardiac surgery; vankomycin; terapie ran pomocí řízeného podtlaku; Tandem Mass Spectrometry; Oxacillin; oxacilin